Stress and Retirees of Higher Education Institutions(HEIs) in Nigeria - Oguzor, Nkasiobi Silas; Adebola, Helen Ebunoluwa; Opara, Jacinta A. (Mediterranean Journal of Social Sciences, 2011)
This study examines a study of stress on retirees. The study also identifies the cause of stress and strategies forreducing stress on retirees at the Federal University Pensioner Association(FUPA), University of Ibadan Chapter. The populationof the study comprised 4000 male and female retirees of (FUPA). The sample of the study was 400 selected from the Universityof Ibadan Chapter using simple random sampling technique. A questionnaire was used for data collection. Data collected wereanalyzed applying frequency counts and mean statistic. Findings revealed that standing for a long time can cause stress forretirees. The finding of the study also revealed that non payment of gratuity and pension can cause stress for retirees. Thefindings of the study further showed eight strategies for reducing stress. Based on the findings recommendations were made.